9:{1,3 3,9}
18:{1,2,3 6,9,18}
(3^8 ⋅ 2^-5 ⋅ 9^0)^-2 ⋅ (2^ -2 / 3^3) ^4 ⋅ 3^28 =
(6561 * 0.03125 * 1)^2 * (0.00925)^4 * 22876792454961 =
42037.81348 * 0.00000000732094 * 22876792454961 =
7040477235.56798349
round answer as needed
Step-by-step explanation:
27^1/3
=(3^3)^1/3
=(3^3)×1/3
=3, so your final answer is D.)27 to the power of 1 over 3 equals 3 to the power of 3 to the power of 1 over 3 equals 3 to the power of 3 multiplied by 1 over 3 equals 3
Or
27^1/3=?
To find the answer, I will use one formula from Laws of Exponent
a^p/q
=q√a^p
Apply the same steps to 27^1/3
27^1/3
=³√27¹
=³√27
=3. Hope it help!
I don’t think this exact answer is there